Method for enriching new pollutants in water through cooperation of microorganisms and free-state manganese
Through the microbial collaborative free state manganese enrichment method, combined with ultrafiltration, pulsed electromagnetic field and nanocellulose crystal composite gel, the problem of difficult degradation of new pollutants in water is solved, and efficient pollutant removal and purification effects are achieved.
Patent Information
- Application Number
- CN202411464278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-13
AI Technical Summary
New pollutants present in the water environment, such as persistent organic pollutants and heavy metals, are difficult to degrade, leading to potential threats to humans and ecosystems, and prior art is difficult to effectively remove these trace but lasting pollutants.
Adopt microorganism collaborative free state manganese enrichment method, and promote the circulation and regeneration of manganese ions and the oxidative degradation of pollutants through ultrafiltration, pulsed electromagnetic field, hydrogen peroxide, nanocellulose crystal composite gel and LED light curing technologies, and combine with microorganisms. biodegradation improves the removal efficiency of new pollutants in water.
It significantly improves the degradation efficiency and purification effect of new pollutants in the water, enhances the anti-pollution ability and service life of the composite gel, and realizes efficient oxidation of difficult-to-degradable substances such as PFASs and synergistic microbial degradation.
Smart Images

Figure CN119118432A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a method for enriching new pollutants in water by using microorganisms in collaboration with free manganese. Background Art
[0002] Emerging contaminants (ECs) refer to organic pollutants that exist in trace amounts in the environment, mainly including persistent organic pollutants, endocrine disruptors and antibiotics, which are potentially harmful to humans, animals and plants. In the past decade, various ECs have been frequently detected in water environments around the world. ECs in surface water usually exist at levels of nanograms to milligrams per liter. Although these ECs have low concentrations in the environment and will not cause serious harm to human health in a short period of time, due to their biodegradability and strong accumulation, they may accumulate and enrich in water bodies and eventually enter the food chain, causing potential and continuous harm to aquatic organisms and humans, and posing a potential threat to human health and ecosystems, thus attracting people's continuous attention. In recent years, due to the discharge of unused and expired medicines, industrial waste, hospital waste and landfill leachate in daily life, the accumulation of emerging contaminants (ECs) in the aquatic environment has increased from ng / L to μg / L.
[0003] New pollutants in water mainly include the following categories: 1. Emerging agricultural pollutants. In recent years, people have paid more and more attention to the environmental risks caused by agricultural activities, such as emerging pollutants such as pesticide residues and veterinary drug residues. 2. Organic water pollutants. With the development of chemical synthesis technology, more and more organic compounds have been found to exist in water bodies, bringing new pollution risks to the water environment. 3. Other emerging pollutants. In addition to agricultural and organic pollutants, some new pollutants such as personal care products, drug residues, microplastics, etc. have also been found to exist in water bodies, posing potential hazards to the water environment and human health; 4. Traditional water pollutants. In addition to emerging pollutants, traditional water pollutants such as heavy metals, nutrients, bacteria, etc. are still the main challenges facing the water environment.
[0004] In order to solve the above problems, the present invention is determined to involve a method for enriching new pollutants in water with microorganisms in collaboration with free manganese to improve the purification effect of new pollutants in water. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for enriching new pollutants in water by using microorganisms in cooperation with free manganese, comprising the following steps:
[0006] S1. Ultrafiltration treatment is performed on the water body to be treated at a pressure of 0.15-0.3 MPa for 8-30 minutes to obtain primary filtered water;
[0007] S2, applying a pulse electromagnetic field with a frequency of 1-50 Hz, a working current of 1-1000 A, and a magnetic induction intensity of 0.01-1 T, then adding a composite gel containing free manganese and nanocellulose crystals into the primary filtered water at a ratio of 0.5-2.5 mg / L, continuously passing hydrogen peroxide into the primary filtered water at a ventilation rate of 1-2 L / min for 15-20 min, then turning off the pulse electromagnetic field, continuing to add microorganisms at a concentration ratio of 0.5-2.5 mg / L, and ultrasonically treating for 30-60 min at an ultrasonic power of 300-400 W, then passing oxygen at a ventilation rate of 0.8-1.2 L / min and simultaneously performing LED light curing treatment for 25-40 min, to obtain secondary filtered water; the ratio of free manganese to nanocellulose crystals is 30-60:1-5;
[0008] S3, shaking the secondary filtered water at 20-30°C and performing reverse osmosis treatment at a pressure of 0.1-0.3 MPa to obtain purified water;
[0009] The free manganese is any one of potassium permanganate, potassium dichromate and manganese dioxide or two of them in equal proportions.
[0010] Description: Under the action of electromagnetic field, hydrogen peroxide can be activated to produce more highly active oxidants such as ·OH (hydroxyl radicals). These free radicals can efficiently oxidize organic pollutants in water, accelerate the degradation process of pollutants, further enhance the oxidation effect, and effectively oxidize and decompose PFAS (perfluorinated and polyfluoroalkyl substances). Pulsed electromagnetic field can promote the recycling and regeneration of manganese ions, maintain its catalytic activity, and thus improve the efficiency of pollutant degradation. Electromagnetic field can change the surface charge distribution of nanocellulose crystals and enhance its adsorption capacity for new pollutants. Stop the pulsed electromagnetic field and introduce oxygen and LED light curing to allow microorganisms to naturally degrade pollutants without external interference, thereby improving their activity and efficiency. In addition, the cavitation effect of ultrasonic treatment is used to generate tiny bubbles. When the bubbles burst, energy is released, destroying the structure of pollutants, accelerating microbial degradation, improving the effect of microorganisms in filtering new pollutants in water, and improving the water filtration stability of microorganisms.
[0011] Furthermore, in step S1, the pore size of the ultrafiltration membrane is in the range of 0.01 to 0.02 μm, and the flux is in the range of 10 to 30 L / m 2 h; In step S3, the pore size of the reverse osmosis membrane is 80 to 120 nm;
[0012] Note: The above-mentioned pore size and flux limitations can ensure that suspended matter and microplastics in new pollutants in water are effectively removed. Ultrafiltration can remove larger suspended particles and some microorganisms, while reverse osmosis can further remove smaller pollutant molecules, thereby improving the purification effect.
[0013] Furthermore, the preparation method of the composite gel containing free manganese and nanocellulose crystals is as follows: reducing graphene oxide, free manganese and polyvinyl alcohol are ultrasonically mixed at a mass ratio of 5 to 10: 0.1 to 3: 5 to obtain a mixed solution A, and then the nanocellulose crystals are added and mixed at a ratio of 3 to 10 mL: 1 g of the mixed solution A: nanocellulose crystals to obtain a suspension, centrifugally stirring at a speed of 8000 to 10000 r / min for 2.5 to 3.5 hours, and freeze-thaw drying to generate a three-dimensional porous gel;
[0014] Then, a layer of magnetic chitosan particles is sprayed on the surface of the three-dimensional porous gel, and heat-treated at a temperature of 70 to 90° C. for 30 to 60 minutes to obtain a composite gel containing free manganese and nanocellulose crystals. The nozzle diameter of the spray gun is 0.7 to 1 mm, the exhaust pressure is 25 to 40 psi, the movement speed of the spray gun is 1 to 1.8 cm / s, the spraying time is 1 to 2 seconds each time, and the spraying amount of the magnetic chitosan particles is 25 to 40 g / m 2 .
[0015] The magnetic chitosan particles are composed of chitosan solution with a mass concentration of 1.5-2.5%, Fe3O4 particles, liquid paraffin, and glutaraldehyde in a volume ratio of 1:1:0.3-0.5:0.1-0.2; the particle size of the magnetic chitosan particles is 0.02-0.05 μm;
[0016] Description: When an external magnetic field is applied, the magnetic aerogel is rapidly attracted and gathered in the area of action of the magnetic field due to the directional arrangement of the magnetic moments of its magnetic components, thereby achieving efficient adsorption of pollutants; this adsorption process can quickly adjust the efficiency of adsorption. During the desorption process, after the external magnetic field is removed, the magnetic components in the composite gel lose the driving force of the magnetic moment orientation, and the aerogel can be desorbed by simple mechanical stirring or the reverse action of the external magnetic field. After desorption, the composite gel can be recovered and regenerated in an environment without a magnetic field for next use.
[0017] Chitosan and its magnetic composite materials have high chemical stability in water treatment and can maintain structural stability under different pH values and temperature conditions, which is very beneficial for treating variable water quality conditions. The synergistic effect of nanocellulose crystals and free manganese can effectively improve the anti-pollution ability of the gel and extend the service life of the gel. At the same time, the hydrophilicity and electronegativity of the prepared composite gel can also be enhanced. At this time, loading magnetic chitosan particles on the surface of the gel can increase the magnetic responsiveness of the composite material and facilitate recovery. The polysaccharide structure of chitosan can form hydrogen bonds or electrostatic interactions with pollutants to enhance the adsorption effect; at the same time, the electromagnetic field induces the vibration of the magnetic particles, further enhancing their interaction with pollutants, improving the adsorption rate and efficiency, thereby improving the membrane's ability to remove new pollutants and anti-pollution capabilities.
[0018] Furthermore, the parameters of the ultrasonic mixing are: ultrasonic power: 300-400W, ultrasonic temperature: 25-30°C, mixing time: 2.5-3h;
[0019] Note: The above ultrasonic parameters can effectively accelerate the degradation of new pollutants in water by microorganisms and improve the ability of microorganisms to remove new pollutants in water.
[0020] Furthermore, the magnetic chitosan particles are modified before spraying.
[0021] The modification method is:
[0022] First, a corn stalk extract with a concentration of 50 to 90 μg / mL and a winter mallow seed extract with a concentration of 1.5 to 15 μg / mL are mixed to obtain a composite extract;
[0023] The magnetic chitosan particles are immersed in a NaOH aqueous solution with a mass concentration of 8-12%, and then the temperature is adjusted to 40-50°C, stirred for 1-3 hours, washed with deionized water until neutral, and then transferred to a high-pressure homogenizer for homogenization at 500-1500 bar for 10-30 times, and then a layer of composite extract with a thickness of 0.3-0.5 μm is deposited on the surface of the magnetic chitosan particles, and heat-treated at a temperature of 30-40°C for 15-20 minutes to obtain modified magnetic chitosan particles.
[0024] Description: The modification of magnetic chitosan particles can make them exhibit superparamagnetic characteristics. Through its unique three-dimensional network structure, it provides a large number of active adsorption sites, increases the contact area with pollutants, and thus improves the adsorption efficiency. It can also improve the mechanical properties of the material, improve the compatibility and adhesion between the magnetic chitosan particles and the composite gel, thereby optimizing the stability of the composite gel; and the introduction of chitosan particles allows the composite gel to be quickly separated by an external magnetic field, which is easy to recover and reuse, and improves the processing efficiency and economy.
[0025] Furthermore, it is characterized in that the nanocellulose crystals are subjected to a thermorheological treatment before being added, the thermorheological environment temperature is 150-200° C., and the rheological speed is 0.5-2.0 mm / min;
[0026] Note: Rheological treatment can also induce the self-assembly of nanocellulose crystals to form nanofiber materials with structural colors. It can also reduce viscosity and increase fluidity, thereby improving the adsorption effect of the gel.
[0027] Furthermore, the freeze-thaw drying method is as follows: freeze-drying the gel precursor obtained by centrifugal stirring at -220 to -180°C, thawing in a water bath at 25 to 35°C, and repeatedly freezing and thawing 5 to 7 times, and performing a smoothing treatment after each freeze-thaw, wherein the smoothing treatment is to use high-pressure water with a pressure of 0.8 to 1 MPa to flush the surface of the gel precursor for 3 to 10 minutes, then rinse with deionized water 1 to 3 times, and then place it in a protective atmosphere and dry it for 2 to 6 minutes;
[0028] Description: Freeze-thaw cycles and smoothing treatment followed by drying under a protective atmosphere help stabilize the porous structure of the gel, prevent structural collapse, and ensure the structural integrity and stability of the gel during the adsorption process, thereby improving the durability of the composite gel containing free manganese and nanocellulose crystals during use; smoothing treatment not only removes surface impurities through high-pressure water flushing, but also optimizes the surface hydrophilicity of the gel, which helps to improve the interaction between the gel and water and new pollutants, and enhances the adsorption capacity.
[0029] Furthermore, the preparation method of the corn stalk extract is:
[0030] The corn stalks are crushed into powders with a mesh size of 100, and the corn stalks are treated with a NaOH solution with a concentration of 2 to 3 mol / L at a temperature of 70 to 80°C for 3 to 3.2 hours, and the solid is separated to obtain black liquor, and the black liquor is rotary evaporated to separate the liquid to obtain lignin, and then a mixed solution obtained by using water and ethanol in a ratio of 1 to 3:7 to 9 is used as a medium, and the lignin and the medium are mixed to obtain a corn stalk extract with a concentration of 50 to 90 μg / mL; the mass ratio of the NaOH solution to the corn stalks is 10 to 12:5; the rotary evaporation temperature is 70 to 80°C, the pressure is 0.05 to 0.08 MPa, the rotation speed is 95 to 120 r / min, and the rotary evaporation time is 25 to 35 min;
[0031] The preparation method of the Malva ovata seed extract is as follows:
[0032] The winter mallow seeds are screened and cleaned, shelled, steamed and fried at 40-60° C. for 20-40 minutes, and sent to a press at a pressing temperature of 65-85° C. for 60-120 minutes. After pressing, an oil extract is obtained, and then a mixed solution of water and ethanol in a ratio of 1-3:7-9 is used as a medium, and the oil extract and the medium are mixed to obtain 1.5-15 μg / mL of winter mallow seed extract;
[0033] Description: Mixing lignin extracted from corn stalks with the medium can significantly improve the adsorption effect of the gel. Lignin has a significant adsorption effect on heavy metal ions and organic matter in agricultural water. In addition, the introduction of lignin can also improve the mechanical strength of the gel, making it more stable and durable in practical applications. The magnetic chitosan particles can be mixed with lignin extracted from corn stalks to improve the adsorption efficiency and stability of the magnetic chitosan particles, thereby maintaining a high performance in the adsorption-desorption cycle, which not only reduces the consumption of materials, but also helps to reduce the cost of environmental governance. Winter mallow seed oil extract can improve the stability of the magnetic chitosan particles by forming a protective layer and reduce structural damage during the adsorption and desorption process.
[0034] Direct use of lignin may not be tightly bound to the magnetic chitosan particles due to its structural complexity and low reactivity, thus affecting the adsorption effect. We mixed it with a mixture of water and ethanol. The introduction of ethanol will affect the distribution and interaction of magnetic nanoparticles in the magnetic chitosan particles, thereby affecting the saturation magnetization intensity and hysteresis loop of the particles, further enhancing its magnetization effect, so as to achieve the regeneration and reuse of the adsorbent.
[0035] Furthermore, the microorganisms include, by mass percentage, 25-35% of Rhodobacter strain NP25, 25-35% of marine isolated strain Bacillus Velez MHNK1, 1-5% of Halomonas smyrna and the remainder of Lactobacillus plantarum Z7.
[0036] Description: Rhodobacter strain NP25 has a high degradation rate for nonylphenol polyoxyethylene ether, and the marine isolate Bacillus Velez MHNK1 has a strong degradation rate for ATZ. PFASs (perfluorinated and polyfluoroalkyl substances) are persistent organic pollutants (POPs) in water. Due to their chemical stability, PFASs are difficult to degrade in water bodies and can migrate over long distances and be widely distributed. During its growth, Halomonas smyrnensis releases ammonia and carbonic anhydrase to increase the pH value to 8.80, significantly promoting the precipitation of calcium ions. Lactobacillus plantarum Z7 is used to enrich calcium ions in water, thereby converting PFASs into non-toxic calcium fluoride. This method shows high efficiency and environmental friendliness.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention first utilizes an ultrafiltration membrane to filter out larger suspended particles and some microorganisms in the water, and then utilizes a pulsed electromagnetic field, a composite gel containing free manganese and nanocellulose crystals, and hydrogen peroxide to synergistically efficiently oxidize organic pollutants in the water. The pulsed electromagnetic field can promote the recycling and regeneration of manganese ions, maintaining its catalytic activity to achieve effective degradation of PFASs in the water, and then further degrades the intermediates or by-products generated in the process of degrading PFASs through the synergistic effect of oxygen, LED light curing, and microorganisms. At the same time, other new pollutants in the water are effectively treated. Oxygen provides additional oxidants, LED light curing can stimulate photocatalytic reactions, and promote the decomposition of pollutants. The introduction of microorganisms utilizes the principle of biodegradation to further improve the treatment efficiency and thoroughness.
[0039] (2) The present invention introduces magnetic chitosan particles during the preparation of the composite gel containing free manganese and nanocellulose crystals, which can quickly adjust the adsorption efficiency during the adsorption process. After desorption, the particles are recovered and regenerated in a magnetic field-free environment for next use, thereby effectively improving the environmental protection and economic efficiency of the composite gel. The synergistic effect of the nanocellulose crystals and free manganese can effectively improve the anti-pollution ability of the gel and extend the service life of the gel. At the same time, the hydrophilicity and electronegativity of the prepared composite gel can also be enhanced, further enhancing its interaction with new pollutants in water and improving the adsorption rate and efficiency of the composite gel. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a degradation effect diagram of the purification method of Examples 1 to 25 of the present invention and Comparative Examples 1 to 5;
[0041] Figure 2 It is a degradation effect diagram of the purification method of Example 1, Example 26 to Example 31 and Comparative Example 6 to Comparative Example 7 of the present invention;
[0042] Figure 3 It is a degradation stability effect diagram of the purification methods of Example 1, Examples 26 to 31 and Comparative Examples 6 to 7 of the present invention. DETAILED DESCRIPTION
[0043] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0044] Example 1: A method for enriching new pollutants in water by using microorganisms in cooperation with free manganese, comprising the following steps:
[0045] S1. Ultrafiltration treatment is performed on the water to be treated at a pressure of 0.22 MPa for 15 minutes to obtain primary filtered water; in step S1, the pore size range of the ultrafiltration membrane is 0.01-0.02 μm, and the flux is 20 L / m 2 h;
[0046] S2, applying a pulsed electromagnetic field with a frequency of 25 Hz, a working current of 500 A, and a magnetic induction intensity of 0.5 T, and then adding a composite gel containing free manganese and nanocellulose crystals into the primary filtered water at a ratio of 1.2 mg / L, and continuously passing hydrogen peroxide into the primary filtered water at a ventilation rate of 1.5 L / min for 18 minutes, and then turning off the pulsed electromagnetic field, and continuing to add microorganisms at a concentration ratio of 1.3 mg / L, and ultrasonically treating for 45 minutes under the condition of an ultrasonic power of 350 W, and then passing oxygen at a ventilation rate of 1.0 L / min and simultaneously performing LED light curing treatment, the curing treatment time is 32 minutes, and obtaining secondary filtered water; the ratio of free manganese to nanocellulose crystals is 15:1;
[0047] The preparation method of the composite gel containing free manganese and nanocellulose crystals is as follows: reducing graphene oxide, free manganese and polyvinyl alcohol are ultrasonically mixed at a mass ratio of 8:1.6:5 to obtain a mixed solution A, and then nanocellulose crystals are added and mixed at a ratio of 6mL:1g of the mixed solution A: nanocellulose crystals to obtain a suspension, centrifugally stirred for 3h at a speed of 9000r / min, and freeze-thawed and dried to generate a three-dimensional porous gel; the parameters of ultrasonic mixing are: ultrasonic power: 350W, ultrasonic temperature: 28℃, mixing time: 2.8h; before adding nanocellulose crystals, the nanocellulose crystals are subjected to thermorheological treatment, the thermorheological environment temperature is 175℃, and the rheological velocity is 1.2mm / min;
[0048] The freeze-thaw drying method is as follows: freeze-dry the gel precursor obtained by centrifugal stirring at -200°C, thaw in a water bath at 30°C, and repeat freeze-thaw for 6 times. After each freeze-thaw, perform a smoothing treatment. The smoothing treatment is to use high-pressure water with a pressure of 0.9 MPa to flush the surface of the gel precursor for 6 minutes, then rinse with deionized water twice, and then dry it under a protective atmosphere for 4 minutes.
[0049] Then, a layer of magnetic chitosan particles was sprayed on the surface of the three-dimensional porous gel and heat treated at 80°C for 45 minutes to obtain a composite gel containing free manganese and nanocellulose crystals. The nozzle diameter of the spray gun was 0.9 mm, the exhaust pressure was 32 psi, the movement speed of the spray gun was 1.4 cm / s, the spraying time was 1.5 s each time, and the spraying amount of magnetic chitosan particles was 32 g / m 2 .
[0050] The magnetic chitosan particles are composed of a chitosan solution with a mass concentration of 2%, Fe3O4 particles, liquid paraffin, and glutaraldehyde in a volume ratio of 1:1:0.4:0.15; the particle size of the magnetic chitosan particles is 0.02-0.05 μm;
[0051] S3, shaking the secondary filtered water at 20-30°C and performing reverse osmosis treatment at a pressure of 0.2 MPa, and obtaining purified water after the treatment; in step S3, the pore size of the reverse osmosis membrane is 100 nm;
[0052] Free manganese is potassium permanganate with a commercial concentration of 0.2 to 0.3 mol / L;
[0053] The microorganisms include, by mass percentage, 30% of Rhodobacter strain NP25, 30% of marine isolated strain Bacillus Velez MHNK1, 2.5% of Halomonas smyrna and the balance of Lactobacillus plantarum Z7.
[0054] Example 2: Different from Example 1, in step S1, the water to be treated is ultrafiltered for 8 min at a pressure of 0.15 MPa to obtain primary filtered water; in step S1, the pore size range of the ultrafiltration membrane is 0.01 μm, and the flux is 10 L / m 2 h.
[0055] Example 3: Different from Example 1, in step S1, the water to be treated is ultrafiltered for 30 min at a pressure of 0.3 MPa to obtain primary filtered water; in step S1, the pore size range of the ultrafiltration membrane is 0.02 μm, and the flux is 30 L / m 2 h.
[0056] Embodiment 4: Different from Embodiment 1, in step S2, a pulse electromagnetic field with a frequency of 1 Hz, a working current of 1 A and a magnetic induction intensity of 0.01 T is applied.
[0057] Embodiment 5: Different from Embodiment 1, in step S2, a pulse electromagnetic field with a frequency of 50 Hz, a working current of 1000 A and a magnetic induction intensity of 1 T is applied.
[0058] Example 6: Different from Example 1, in step S2, a composite gel containing free manganese and nanocellulose crystals is added to the primary filtered water at a ratio of 0.5 mg / L, and hydrogen peroxide is continuously passed into the primary filtered water at a ventilation rate of 1 L / min for 15 minutes; the ratio of free manganese to nanocellulose crystals is 30:1.
[0059] Example 7: Different from Example 1, in step S2, a composite gel containing free manganese and nanocellulose crystals is added to the primary filtered water at a ratio of 2.5 mg / L, and hydrogen peroxide is continuously passed into the primary filtered water at a ventilation rate of 2 L / min for 20 minutes; the ratio of free manganese to nanocellulose crystals is 60:5.
[0060] Example 8: Different from Example 1, in step S2, microorganisms are continued to be added at a concentration ratio of 0.5 mg / L, and ultrasonic treatment is carried out for 30 minutes under the condition of ultrasonic power of 300 W, and then oxygen is introduced at a ventilation rate of 0.8 L / min and LED light curing is carried out simultaneously, and the curing treatment time is 25 minutes.
[0061] Example 9: Different from Example 1, in step S2, microorganisms are continued to be added at a concentration ratio of 2.5 mg / L, and ultrasonic treatment is carried out for 60 minutes under the condition of ultrasonic power of 400 W, and then oxygen is introduced at a ventilation rate of 1.2 L / min and LED light curing is carried out simultaneously, and the curing time is 40 minutes.
[0062] Example 10: Different from Example 1, in step S2, the preparation method of the composite gel containing free manganese and nanocellulose crystals is: ultrasonically mix reduced graphene oxide, free manganese and polyvinyl alcohol at a mass ratio of 5:0.1:5 to obtain a mixed solution A, and then add nanocellulose crystals at a ratio of 3mL:1g of mixed solution A: nanocellulose crystals to obtain a suspension, centrifuge and stir for 2.5h at a rotation speed of 8000r / min, and freeze-thaw and dry to generate a three-dimensional porous gel.
[0063] Example 11: Different from Example 1, in step S2, the preparation method of the composite gel containing free manganese and nanocellulose crystals is: ultrasonically mix reduced graphene oxide, free manganese and polyvinyl alcohol at a mass ratio of 10:3:5 to obtain a mixed solution A, and then add the nanocellulose crystals at a ratio of 10mL:1g of the mixed solution A: nanocellulose crystals to obtain a suspension, centrifuge and stir for 3.5h at a rotation speed of 10000r / min, and freeze-thaw and dry to generate a three-dimensional porous gel.
[0064] Example 12: Different from Example 1, in step S2, the parameters of ultrasonic mixing are: ultrasonic power: 300 W, ultrasonic temperature: 25° C., and mixing time: 2.5 h.
[0065] Example 13: Different from Example 1, in step S2, the parameters of ultrasonic mixing are: ultrasonic power: 400 W, ultrasonic temperature: 30° C., and mixing time: 3 h.
[0066] Example 14: Different from Example 1, in step S2, the nanocellulose crystals are subjected to thermorheological treatment before being added, the thermorheological environment temperature is 150° C., and the rheological speed is 0.5 mm / min;
[0067] Example 15: Different from Example 1, in step S2, the nanocellulose crystals are subjected to thermorheological treatment before being added, the thermorheological environment temperature is 200° C., and the rheological speed is 2.0 mm / min.
[0068] Example 16: Different from Example 1, in step S2, the freeze-thaw drying method is: freeze-drying the gel precursor obtained by centrifugal stirring at -220°C, thawing in a water bath at 25°C, and repeating the freeze-thaw process for 5 times, and performing a smoothing process after each freeze-thaw process. The smoothing process is to flush the surface of the gel precursor with high-pressure water at a pressure of 0.8 MPa for 3 minutes, then rinse it with deionized water once, and then dry it under a protective atmosphere for 2 minutes;
[0069] Then, a layer of magnetic chitosan particles is sprayed on the surface of the three-dimensional porous gel, and heat-treated at 70°C for 30 minutes. After the treatment, a composite gel containing free manganese and nanocellulose crystals is obtained.
[0070] Example 17: Different from Example 1, in step S2, the freeze-thaw drying method is: freeze-drying the gel precursor obtained by centrifugal stirring at -180°C, thawing in a water bath at 35°C, and repeating the freeze-thaw process for 7 times, and performing a smoothing process after each freeze-thaw process. The smoothing process is to flush the surface of the gel precursor with high-pressure water at a pressure of 1 MPa for 10 minutes, then rinse with deionized water for 3 times, and then dry it under a protective atmosphere for 6 minutes;
[0071] Then, a layer of magnetic chitosan particles is sprayed on the surface of the three-dimensional porous gel, and heat-treated at 90° C. for 60 minutes. After the treatment, a composite gel containing free manganese and nanocellulose crystals is obtained.
[0072] Example 18: Different from Example 1, in step S2, the nozzle diameter of the spray gun is 0.7 mm, the exhaust pressure is 25 psi, the moving speed of the spray gun is 1 cm / s, the spraying time is 1 s each time, and the spraying amount of the magnetic chitosan particles is 25 g / m 2 .
[0073] Example 19: Different from Example 1, in step S2, the nozzle diameter of the spray gun is 1 mm, the exhaust pressure is 40 psi, the moving speed of the spray gun is 1.8 cm / s, the spraying time is 2 s each time, and the spraying amount of the magnetic chitosan particles is 40 g / m 2 .
[0074] Example 20: Different from Example 1, in step S2, the magnetic chitosan particles are composed of chitosan solution with a mass concentration of 1.5%, Fe3O4 particles, liquid paraffin, and glutaraldehyde in a volume ratio of 1:1:0.3:0.1; the particle size of the magnetic chitosan particles is 0.02-0.05 μm.
[0075] Example 21: Different from Example 1, in step S2, the magnetic chitosan particles are composed of chitosan solution with a mass concentration of 2.5%, Fe3O4 particles, liquid paraffin, and glutaraldehyde in a volume ratio of 1:1:0.5:0.2; the particle size of the magnetic chitosan particles is 0.02-0.05 μm.
[0076] Example 22: Different from Example 1, in step S3, the secondary filtered water is shaken at 20°C and subjected to reverse osmosis treatment at a pressure of 0.1 MPa to obtain purified water; the pore size of the reverse osmosis membrane is 80 nm.
[0077] Example 23: Different from Example 1, in step S3, the secondary filtered water is shaken at 30°C and subjected to reverse osmosis treatment at a pressure of 0.3 MPa to obtain purified water; the pore size of the reverse osmosis membrane is 120 nm.
[0078] Example 24: Different from Example 1, the microorganisms include, by mass percentage, 25% of Rhodobacter strain NP25, 25% of marine isolate Bacillus Velezii MHNK1, 1% of Halomonas smyrna and the remainder of Lactobacillus plantarum Z7.
[0079] Example 25: Different from Example 1, the microorganisms include, by mass percentage, 35% of Rhodobacter strain NP25, 35% of marine isolate Bacillus Velezii MHNK1, 5% of Halomonas smyrna and the remainder of Lactobacillus plantarum Z7.
[0080] Example 26: Different from Example 1, the magnetic chitosan particles are modified before spraying.
[0081] The modification treatment method is:
[0082] First, a corn stover extract with a concentration of 70 μg / mL and a winter mallow seed extract with a concentration of 8 μg / mL were mixed to obtain a composite extract;
[0083] The preparation method of corn straw extract is as follows:
[0084] The corn stalks were crushed into 100 mesh powders, and treated with a 2.5 mol / L NaOH solution at 75°C for 3.1 h to obtain cellulose solids and black liquor, and then the separated black liquor was rotary evaporated, and the sugar liquid was separated to obtain lignin, and then a mixed solution obtained by using water and ethanol in a ratio of 1:4 was used as a medium, and the lignin and the medium were mixed to obtain a corn stalk extract with a concentration of 70 μg / mL; the mass ratio of the NaOH solution to the corn stalks was 11:5; the rotary evaporation temperature was 70-80°C, the pressure was 0.06 MPa, the rotation speed was 105 r / min, and the rotary evaporation time was 30 min;
[0085] The preparation method of winter mallow seed extract is as follows:
[0086] The winter mallow seeds were screened and cleaned, shelled, steamed and fried at 50°C for 30 minutes, and sent to a press at a pressing temperature of 75°C for 90 minutes. After pressing, an oil extract was obtained. A mixed solution of water and ethanol in a ratio of 2:8 was used as a medium, and the oil extract and the medium were mixed to obtain 8 μg / mL of winter mallow seed extract.
[0087] The magnetic chitosan particles were immersed in a 10% NaOH aqueous solution, and then the temperature was adjusted to 45°C, stirred for 2 hours, washed with deionized water until neutral, and then transferred to a high-pressure homogenizer and homogenized 20 times at 1000 bar. Then, a layer of composite extract with a thickness of 0.4 μm was deposited on the surface of the magnetic chitosan particles, and heat treated at 35°C for 18 minutes to obtain modified magnetic chitosan particles.
[0088] Example 27: Different from Example 26, 50 μg / mL corn stalk extract and 1.5 μg / mL wintergreen seed extract were first mixed to obtain a composite extract;
[0089] The preparation method of corn straw extract is as follows:
[0090] The corn stalks were crushed into 100 mesh powders, and treated with a 2 mol / L NaOH solution at 70°C for 3 h to obtain cellulose solids and black liquor, and then the separated black liquor was rotary evaporated, and the sugar liquid was separated to obtain lignin, and then a mixed solution obtained by using water and ethanol in a ratio of 1:7 was used as a medium, and the lignin and the medium were mixed to obtain a corn stalk extract with a concentration of 50 μg / mL; the mass ratio of the NaOH solution to the corn stalks was 2:1; the rotary evaporation temperature was 70°C, the pressure was 0.05 MPa, the rotation speed was 95 r / min, and the rotary evaporation time was 25 min;
[0091] The preparation method of winter mallow seed extract is as follows:
[0092] The winter mallow seeds were screened and cleaned, shelled and steamed at 40°C for 20 minutes, and sent to a press with a pressing temperature of 65°C and a pressing time of 60 minutes. After pressing, an oil extract was obtained, and then a mixed solution of water and ethanol in a ratio of 1:9 was used as a medium, the oil extract and the medium were mixed to obtain 1.5 μg / mL of winter mallow seed extract.
[0093] Example 28: Different from Example 26, the corn stover extract with a concentration of 90 μg / mL and the winter mallow seed extract with a concentration of 15 μg / mL were first mixed to obtain a composite extract;
[0094] The preparation method of corn straw extract is as follows:
[0095] The corn stalks were crushed into 100 mesh powders, and treated with a 3 mol / L NaOH solution at 80°C for 3.2 h to obtain cellulose solids and black liquor, and then the separated black liquor was rotary evaporated, and the sugar liquid was separated to obtain lignin, and then a mixed solution obtained by using water and ethanol in a ratio of 3:9 was used as a medium, and the lignin and the medium were mixed to obtain a corn stalk extract with a concentration of 90 μg / mL; the mass ratio of the NaOH solution to the corn stalks was 12:5; the rotary evaporation temperature was 80°C, the pressure was 0.08 MPa, the rotation speed was 120 r / min, and the rotary evaporation time was 35 min;
[0096] The preparation method of winter mallow seed extract is as follows:
[0097] The winter mallow seeds were screened and cleaned, shelled and steamed at 60°C for 40 minutes, and sent to a press with a pressing temperature of 85°C and a pressing time of 120 minutes. After pressing, an oil extract was obtained, and then a mixed solution of water and ethanol in a ratio of 3:7 was used as a medium, the oil extract and the medium were mixed to obtain 15 μg / mL of winter mallow seed extract.
[0098] Example 29: Different from Example 26, the magnetic chitosan particles are immersed in an aqueous solution of NaOH with a mass concentration of 8%, and then the temperature is adjusted to 40°C, stirred for 1 hour, washed with deionized water until neutral, and then transferred to a high-pressure homogenizer and homogenized at 500 bar for 10 times, and then a layer of composite extract with a thickness of 0.3 μm is deposited on the surface of the magnetic chitosan particles, and heat treated at 30°C for 15 minutes to obtain modified magnetic chitosan particles.
[0099] Example 30: Different from Example 26, the magnetic chitosan particles are immersed in a NaOH aqueous solution with a mass concentration of 12%, and then the temperature is adjusted to 50°C, stirred for 3 hours, washed with deionized water until neutral, and then transferred to a high-pressure homogenizer and homogenized at 1500 bar for 30 times, and then a layer of composite extract with a thickness of 0.5 μm is deposited on the surface of the magnetic chitosan particles, and heat treated at 40°C for 20 minutes to obtain modified magnetic chitosan particles.
[0100] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention. In this example, PFASs are used as the detection object.
[0101] The degradation rate detection method is as follows: firstly, the initial concentration of new pollutants (perfluorinated and polyfluoroalkyl substances) in sewage is detected, and then the sewage is purified by the method, and the purified concentration of perfluorinated and polyfluoroalkyl substances in the purified water is tested, and (initial concentration-purified concentration) / initial concentration is used as the degradation rate of new pollutants of the purification method;
[0102] The method for determining the degradation stability is as follows: the polluted water containing perfluorinated and polyfluoroalkyl substances is degraded 5 times according to the detection method of the present application, and the first degradation rate and the fifth degradation rate are recorded respectively, and the fifth degradation rate / first degradation rate×100% is taken as the degradation stability of the present method;
[0103] 1. Investigate the effect of treatment methods on the degradation rate of per- and polyfluoroalkyl substances in water
[0104] Control Example 1: Different from Example 1, no pulsed electromagnetic field is applied during the composite gel treatment process.
[0105] Control Example 2: Different from Example 1, the composite gel does not contain nanocellulose crystals.
[0106] Control Example 3: Different from Example 1, no smoothing treatment was performed during the freeze-thaw drying process.
[0107] Comparative Example 4: Different from Example 1, the magnetic chitosan particles do not contain glutaraldehyde.
[0108] Comparative Example 5: Different from Example 1, the microorganisms do not contain Smyrna salt monospora.
[0109] Conclusion: Figure 1It can be seen that the treatment methods of Control Examples 1 to 5 have a certain adverse effect on the degradation rate of perfluorinated and polyfluoroalkyl substances in water. Among them, the absence of pulsed electromagnetic field in Control Example 1 will cause the degradation rate of perfluorinated and polyfluoroalkyl substances to decrease. This is because the pulsed electromagnetic field can promote the recycling and regeneration of manganese ions and maintain their catalytic activity, thereby improving the efficiency of pollutant degradation. At the same time, the electromagnetic field can also enhance its adsorption capacity for new pollutants by changing the surface charge distribution of nanocellulose crystals; and nanocellulose crystals have a higher specific surface area, which helps to provide more active sites and promote the adsorption and degradation of organic matter and heavy metal ion pollutants in attached water. Without these crystals, the adsorption capacity of the composite gel will be significantly reduced. The degradation efficiency is significantly decreased, thereby affecting the degradation efficiency; in Control Example 3, impurities may remain on the surface of the gel due to the lack of a smoothing step, thereby weakening its adsorption capacity; in Control Example 4, when glutaraldehyde is not present, the magnetism of the Fe3O4 particles remains unchanged, but the physical stability of the three-dimensional network structure of chitosan may be reduced and become looser, which may indirectly affect the distribution and fixation of the magnetic particles in the gel, thereby reducing the adsorption of PFASs; in Control Example 5, the absence of Smyrna salt monosporus in the microorganisms will cause the stability and regeneration ability of the microorganisms to decrease; the stability and regeneration ability of the microbial adsorbent may be improved due to the action of Smyrna salt monosporus, and the lack of this strain may affect the long-term use effect of the adsorbent.
[0110] 2. To investigate the effect of modification of magnetic chitosan particles on the degradation rate and degradation stability of perfluoroalkyl and polyfluoroalkyl substances in water
[0111] Control Example 6: Different from Example 26, the composite extract does not contain the Malva ovata seed extract.
[0112] Control Example 7: Different from Example 26, no homogenization treatment was performed.
[0113] Conclusion: Figure 2 , Figure 3From the comparison of Example 1, Examples 26 to 30 and Control Examples 6 to 7, it can be seen that the modification of the magnetic chitosan particles can effectively improve the degradation rate and degradation stability of perfluorinated and polyfluoroalkyl substances in water, while in Control Example 6, the magnetic chitosan particles lack the protective layer provided by the winter mallow seed extract, and may be more likely to agglomerate, reducing their dispersibility in water, thereby affecting the adsorption stability, and due to the lack of the mechanical strength enhanced by the winter mallow seed extract, the composite gel may be more easily damaged, resulting in the loss of the adsorbent, affecting the long-term adsorption effect; the absence of the winter mallow seed extract also reduces the additional adsorption sites, thereby reducing the adsorption capacity of the composite gel for perfluorinated and polyfluoroalkyl substances. In Control Example 7, the particles that have not been homogenized may have unevenly distributed sediments, affecting the adsorption effect, and the homogenization treatment ensures that the magnetic chitosan particles are more evenly dispersed in the composite gel. If this step is omitted, the particles may agglomerate, resulting in uneven areas in the composite material, which will reduce the overall adsorption efficiency and stability of the material. In Example 26, the magnetic chitosan particles are homogenized and then corn straw extract and winter melon seed extract are deposited on the surface, which can more evenly cover the surface of the particles and enhance their ability to adsorb PFASs.
Claims
1. A method for enriching new pollutants in water by using microorganisms in cooperation with free manganese, characterized in that: The following steps are involved: S1. Ultrafiltration treatment is performed on the water body to be treated at a pressure of 0.15-0.3 MPa for 8-30 minutes to obtain primary filtered water; S2, applying a pulse electromagnetic field with a frequency of 1-50 Hz, a working current of 1-1000 A, and a magnetic induction intensity of 0.01-1 T, then adding a composite gel containing free manganese and nanocellulose crystals into the primary filtered water at a ratio of 0.5-2.5 mg / L, continuously passing hydrogen peroxide into the primary filtered water at a ventilation rate of 1-2 L / min for 15-20 min, then turning off the pulse electromagnetic field, continuing to add microorganisms at a concentration ratio of 0.5-2.5 mg / L, and ultrasonically treating for 30-60 min at an ultrasonic power of 300-400 W, then passing oxygen at a ventilation rate of 0.8-1.2 L / min and simultaneously performing LED light curing treatment for 25-40 min, to obtain secondary filtered water; the ratio of free manganese to nanocellulose crystals is 30-60:1-5; S3, shaking the secondary filtered water at 20-30°C and performing reverse osmosis treatment at a pressure of 0.1-0.3 MPa to obtain purified water; The free manganese is any one of potassium permanganate, potassium dichromate and manganese dioxide or two of them in equal proportions.
2. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 1, characterized in that: In step S1, the pore size of the ultrafiltration membrane is in the range of 0.01 to 0.02 μm, and the flux is in the range of 10 to 30 L / m 2 h; In step S3, the pore size of the reverse osmosis membrane is 80 to 120 nm.
3. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 1, characterized in that: The preparation method of the composite gel containing free manganese and nanocellulose crystals is as follows: reducing graphene oxide, free manganese and polyvinyl alcohol are ultrasonically mixed at a mass ratio of 5 to 10:0.1 to 3:5 to obtain a mixed solution A, and then the nanocellulose crystals are added and mixed at a ratio of 3 to 10 mL:1 g of the mixed solution A to the nanocellulose crystals to obtain a suspension, centrifugally stirring for 2.5 to 3.5 hours at a rotation speed of 8000 to 10000 r / min, and freeze-thawing and drying to generate a three-dimensional porous gel; Then, a layer of magnetic chitosan particles is sprayed on the surface of the three-dimensional porous gel, and heat-treated at a temperature of 70 to 90° C. for 30 to 60 minutes to obtain a composite gel containing free manganese and nanocellulose crystals. The nozzle diameter of the spray gun is 0.7 to 1 mm, the exhaust pressure is 25 to 40 psi, the movement speed of the spray gun is 1 to 1.8 cm / s, the spraying time is 1 to 2 seconds each time, and the spraying amount of the magnetic chitosan particles is 25 to 40 g / m 2 . The magnetic chitosan particles are composed of chitosan solution with a mass concentration of 1.5-2.5%, Fe3O4 particles, liquid paraffin and glutaraldehyde in a volume ratio of 1:1:0.3-0.5:0.1-0.2; the particle size of the magnetic chitosan particles is 0.02-0.05 μm.
4. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 3, characterized in that: The parameters of the ultrasonic mixing are: ultrasonic power: 300-400W, ultrasonic temperature: 25-30°C, and mixing time: 2.5-3h.
5. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 3, characterized in that: The magnetic chitosan particles are modified before spraying. The modification method is: First, a corn stalk extract with a concentration of 50 to 90 μg / mL and a winter mallow seed extract with a concentration of 1.5 to 15 μg / mL are mixed to obtain a composite extract; The magnetic chitosan particles are immersed in a NaOH aqueous solution with a mass concentration of 8-12%, and then the temperature is adjusted to 40-50°C, stirred for 1-3 hours, washed with deionized water until neutral, and then transferred to a high-pressure homogenizer for homogenization at 500-1500 bar for 10-30 times, and then a layer of composite extract with a thickness of 0.3-0.5 μm is deposited on the surface of the magnetic chitosan particles, and heat-treated at a temperature of 30-40°C for 15-20 minutes to obtain modified magnetic chitosan particles.
6. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 3, characterized in that: Before adding the nanocellulose crystals, the nanocellulose crystals are subjected to a thermorheological treatment, the thermorheological environment temperature is 150-200° C., and the rheological velocity is 0.5-2.0 mm / min.
7. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 3, characterized in that: The freeze-thaw drying method is as follows: freeze-dry the gel precursor obtained by centrifugal stirring at -220 to -180°C, thaw in a water bath at 25 to 35°C, and repeat freezing and thawing 5 to 7 times. After each freeze-thaw, a smoothing treatment is performed. The smoothing treatment is to use high-pressure water with a pressure of 0.8 to 1 MPa to flush the surface of the gel precursor for 3 to 10 minutes, then rinse with deionized water 1 to 3 times, and then place it in a protective atmosphere to dry for 2 to 6 minutes.
8. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 5, characterized in that: The preparation method of the corn stalk extract is: The corn stalks are crushed into powders with a mesh size of 100, and the corn stalks are treated with a NaOH solution with a concentration of 2 to 3 mol / L at a temperature of 70 to 80°C for 3 to 3.2 hours, and the solid is separated to obtain black liquor, and the black liquor is rotary evaporated to separate the liquid to obtain lignin, and then a mixed solution obtained by using water and ethanol in a ratio of 1 to 3:7 to 9 is used as a medium, and the lignin and the medium are mixed to obtain a corn stalk extract with a concentration of 50 to 90 μg / mL; the mass ratio of the NaOH solution to the corn stalks is 10 to 12:5; the rotary evaporation temperature is 70 to 80°C, the pressure is 0.05 to 0.08 MPa, the rotation speed is 95 to 120 r / min, and the rotary evaporation time is 25 to 35 min; The preparation method of the Malva ovata extract is as follows: The winter mallow seeds are screened and cleaned, shelled, steamed and fried at 40-60°C for 20-40 minutes, and sent to a press with a pressing temperature of 65-85°C and a pressing time of 60-120 minutes. After the pressing, an oil extract is obtained, and then a mixed solution of water and ethanol in a ratio of 1-3:7-9 is used as a medium, and the oil extract and the medium are mixed to obtain 1.5-15 μg / mL of winter mallow seed extract.
9. The method for enriching new pollutants in water by using microorganisms in cooperation with free manganese as claimed in claim 1, characterized in that: The microorganisms include, by mass percentage, 25-35% of Rhodobacter strain NP25, 25-35% of marine isolated strain Bacillus Velez MHNK1, 1-5% of Smyrna saltomonas and the remainder of Lactobacillus plantarum Z7.
Citation Information
Patent Citations
Preparation method of cellulose nanocrystal / graphene / polyvinyl alcohol aerogel
CN108579626A
Preparation method and application of corn stalk core regenerated cellulose immobilized nano-CuS / TiO2 composite aerogel
CN111215143A
Photosensitive magnetic topological structure hydrogel evaporator, preparation method and application thereof
CN115350653A
Extraction and separation method of corn straw lignin
CN117866227A
Method for preparing aerogel by using crosslinking-agent-free Pickering emulsion template and application of aerogel
CN119144042A
